Endometrial 'scratching': what the data show. Issue 4 (August 2016) - Santamaria, Xavier; Katzorke, Nora; Simón, Carlos
Abstract : Purpose of review: Since its first description in 2003, the endometrial scratching procedure has been the topic of over 1000 studies. This procedure, used to improve endometrial receptivity for assisted reproduction, is accessible – any gynecologist can easily perform it – and has been adapted into clinical routine by some reproductive units. However, the available data are controversial, and no biological plausibility exists to support the use of this intervention. This study aims to critically review the existing data, focusing on the last 2 years, regarding the efficiency of endometrial scratching. Recent findings: A total of five randomized controlled studies, one meta-analysis, and a systematic review related to endometrial scratching/injury were published in 2014 and 2015. Considerable heterogeneity exists among these studies regarding the selected population, type of treatment, and even timing and devices used to perform the endometrial injury. Importantly, none of these studies reported improved reproductive outcomes in terms of live birth rates following endometrial scratching. Summary: Overall, data from properly designed and powered randomized controlled studies demonstrate no beneficial effect of this intervention that is based on unknown biological effects. Endometrial scratching produces pain, costs money, and the side-effects of systematic scratching in the production of Asherman syndrome remain to be seen. Think before scratching.